Application of Building Information Modelling (BIM) Technology in Drainage System Using Autodesk InfraWorks 360 Software - King Kuok, Kuok; Kingston Tan Kia, Wee; Chiu, Po Chan; Chin, Mei Yun; Md. Rezaur, Rahman; Muhammad Khusairy, Bakri (Springer Nature Singapore Pte Ltd, 2023)
The increased number of physical drainage drawings at Samarahan district, Sarawak for new development areas is difficult to manage and handle by relevant authorities. Hence, this research is conducted to determine the feasibility of Building Information Technology (BIM) to create a proper drainage inventory system to accurately list and record current drainage information using Autodesk Infraworks 360 software. This inventory system will be employed to examine and validate corresponding drainage parameters based on the recorded information. Taman UniCentral, a residential neighbourhood in Kota Samarahan, has been chosen for this case study. Drainage data, such as drainage size, length, invert level, are entered into GIS-integrated Model Builder in Autodesk InfraWorks 360. Autodesk InfraWorks 360 will conduct a preliminary analysis, including watershed analysis, to delineate the catchment area and drainage performance inspections at rainfall intensities of 2, 5, 10, 20, and 50 years (ARI). Thereafter, the InfraWorks model will be exported into Autodesk Civil3D to conduct a more extensive hydraulic analysis. The results show that full integration of these two Autodesk software packages had created a proper inventory system of existing drainage information and simulated its sufficiency in catering surcharge runoff from the new development area at the upper catchment.